1989
DOI: 10.1104/pp.89.4.1079
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Analog 1-Deoxymannojirimycin Inhibits the Golgi-Mediated Processing of Bean Storage Glycoproteins

Abstract: The asparagine-linked oligosaccharide chains of glycoproteins can be processed to form a wide variety of structures. The Golgi complex is the main compartment involved in this processing. In mammalian cells the first enzyme acting along the Golgi processing pathway is mannosidase 1, whose action is a prerequisite for any further processing and which is inhibited by the mannose analog 1-deoxymannojirimycin (dMM). To have insights into the processing pathway in plant cells, we have studied the In vivo effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…This is consistent with the idea that GRPs are induced by the presence of unfolded proteins in the ER, since negative processes occurring in the Golgi complex or later are not likely to be circumvented by the action of proteins which reside in an earlier compartment of the secretory pathway. As already observed in mammalian cells, the synthesis of bean GRPs is not significantly affected by treatment with dMM, an inhibitor of both mammalian (Fuhrmann et a/., 1984) and plant (Vitale et a/., 1989a) Golgi-mediated processing. We had previously shown that dMM fully inhibits processing of the carbohydrate chains of PHSL and PHA (Vitale et a/., 1989a).…”
Section: Tunicamycin-inducible Proteins In the Er Of Developing Bean supporting
confidence: 74%
See 1 more Smart Citation
“…This is consistent with the idea that GRPs are induced by the presence of unfolded proteins in the ER, since negative processes occurring in the Golgi complex or later are not likely to be circumvented by the action of proteins which reside in an earlier compartment of the secretory pathway. As already observed in mammalian cells, the synthesis of bean GRPs is not significantly affected by treatment with dMM, an inhibitor of both mammalian (Fuhrmann et a/., 1984) and plant (Vitale et a/., 1989a) Golgi-mediated processing. We had previously shown that dMM fully inhibits processing of the carbohydrate chains of PHSL and PHA (Vitale et a/., 1989a).…”
Section: Tunicamycin-inducible Proteins In the Er Of Developing Bean supporting
confidence: 74%
“…As already observed in mammalian cells, the synthesis of bean GRPs is not significantly affected by treatment with dMM, an inhibitor of both mammalian (Fuhrmann et a/., 1984) and plant (Vitale et a/., 1989a) Golgi-mediated processing. We had previously shown that dMM fully inhibits processing of the carbohydrate chains of PHSL and PHA (Vitale et a/., 1989a). This further supports our conclusion that bean GRPs are the functional homologs of mammalian GRPs, and also complements the cell fractionation experiments in locating these proteins as residents of the ER.…”
Section: Tunicamycin-inducible Proteins In the Er Of Developing Bean supporting
confidence: 74%
“…Soil properties are major factors that govern ecosystem processes (Chapin, Matson, and Mooney 2002) and are of paramount importance for ground dwelling animals. The characteristics of soil within the habitat could be the main determinants of habitat use (Parer 1985;Vitale, Zoppe, and Bollini 1989;McCarley 1966;Scharff and Burda 1998).For burrowing mammals, the physical property of the soil determines basically if digging is feasible. However, soil properties and morphology are also influenced by several factors e.g.…”
Section: Soilmentioning
confidence: 99%
“…Oryctolagus cuniculus which digs its burrow system under the roots of Juniperus communis (Parer 1985;Altbäcker, Nyéki, and Kertész 1997)). These shelters and resting places are more durable than burrows in the seahore sand dunes (Vitale, Zoppe, and Bollini 1989). Another pictorial example of soil disturbance by vertebrate animals (biopedturbation) is the burrows and mounds of many subterranean, fossorial, and semi-fossorial mammals.…”
Section: Soilmentioning
confidence: 99%